Pollen morphology of the genus Oxytropis DC. in Turkey - Ceter, Talip; Erkul, Seher Karaman; Aytac, Zeki; Baser, Birol (Bangladesh Journal of Botany, 2013)
Pollen morphology of 11 species of the genus Oxytropis DC. (Fabaceae) distributed in Turkey were examined with light (LM) and scanning electron microscope (SEM). Morphology of pollen grains shows isopolar, radially symmetric, tricolporate, prolate or subprolate, porus shape oblate or operculate and exine subtectate. The size varies with the polar axis from 19.52 - 33.31 ?m and the equatorial axis from 13.50 - 25.82 ?m. There are five ornamentation types: perforate at equatorial section and psilate at polar sections, microreticulate at equatorial sections and psilate at polar sections, microreticulate at equatorial sections and perforate at polar sections, microreticulate at both equatorial and polar sections and perforate at both equatorial and polar sections. Pollen aperture, shape and especially different ornamentation patterns at polar and equatorial section of pollen, as found in this study, appear to be important character. The findings of this study indicate the taxonomic implications of pollen morphology in understanding the similarity and relationships in the genus Oxytropis. DOI: http://dx.doi.org/10.3329/bjb.v42i1.15908 Bangladesh J. Bot. 42(1): 167-174, 2013 (June)